1998
DOI: 10.1111/j.1751-1097.1998.tb03251.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypocrellin A Photosensitization Involves an Intracellular pH Decrease in 3T3 Cells

Abstract: The fluorescent pH probe carboxy-seminaphtorhodafluor-1 (C-Snarf-1) has been used for laser microspectro-fluorometric assays of intracellular pH in 3T3 mouse fibroblasts treated with hypocrellin A. These results are compared to those previously obtained with the structurally related hydroxylated polycyclic quinone, hypericin (Sureau et al., J. Am. Chem. Soc. 118, 9484-9487, 1996). A mean local intracellular pH drop of 0.6 units has been observed in the presence of 1 microM hypocrellin A after 90 s of exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 35 publications
0
44
0
1
Order By: Relevance
“…Adherent mouse fibroblasts (3T3) were used for these experiments. Cell culture samples were prepared as previously described [20]. Through the microscope (Nikon Optiphot‐2), fluorescent cell images were recorded using a 60×1.4 NA oil immersion objective (Nikon).…”
Section: Methodsmentioning
confidence: 99%
“…Adherent mouse fibroblasts (3T3) were used for these experiments. Cell culture samples were prepared as previously described [20]. Through the microscope (Nikon Optiphot‐2), fluorescent cell images were recorded using a 60×1.4 NA oil immersion objective (Nikon).…”
Section: Methodsmentioning
confidence: 99%
“…One of the most interesting photophysical processes that these molecules execute is excited-state proton or H atom transfer, both intramolecular [6][7][8][9][10][11][12][13][14][15][16][17][18][19] and intermolecular. [20][21][22] We have suggested that the intermolecular proton transfer plays a role in certain aspects of the biological activity of hypericin and hypocrellin. 20,[23][24][25] Among the most convincing evidence that intramolecular H atom transfer occurs in hypericin is the observation of a ∼10 ps rise time in the fluorescence upconversion signal of hypericin in DMSO.…”
Section: Introductionmentioning
confidence: 99%
“…18 Of special relevance to the role of labile protons for the lightinduced biological activity of hypericin is the observation that hypericin acidifies its surroundings upon light absorption. [26][27][28][29][30] The role of photogenerated protons takes on additional signifi- …”
mentioning
confidence: 99%